The impact of symptom clusters on endocrine therapy adherence in patients with breast cancer - Sommer Agnew; Megan Crawford; Iain MacPherson; Victor Shiramizu; Leanne Fleming (Breast, 2024)
Background: When taken as prescribed, endocrine therapy is effective in reducing risk of recurrence and mortality in the treatment of patients with breast cancer. However, treatment side effects can act as a barrier to medication adherence. Existing research has not identified any specific side effects as consistent predictors of nonadherence. Our aim was to explore the influence of symptom clusters on self-reported adherence in patients with breast cancer. Methods: A cross-sectional online survey was conducted, including patients with breast cancer currently or previously prescribed endocrine therapy (N = 1051). This included measures of self-reported endocrine therapy adherence and common symptoms among this population (insomnia, depression, anxiety, fatigue, musculoskeletal, and vasomotor symptoms). Results: Unintentional nonadherence was higher than intentional nonadherence (50.8 % vs 31.01 %). The most troublesome symptom was insomnia (73.83 % displayed probable insomnia disorder). K-means cluster analysis identified 2 symptom clusters: overall High symptoms, and overall Low symptoms. Participants in the Low symptoms cluster were significantly more likely to be classed as adherent based on unintentional and intentional items. Conclusions: Nonadherence was high in the current sample, and significantly more likely in participants reporting overall severe symptoms. Clinicians should be aware of the scale of common side effects and facilitate open conversation about potential barriers to adherence. Follow-up care should include assessment of common symptoms and signpost patients to appropriate support or treatment when required. Future research should explore potential for a central symptom to act as a target for intervention, to relieve overall side effect burden and facilitate better medication adherence.